Analyzing requisition–compensation balance of farmland policy in China through telecoupling: A case study in the middle reaches of Yangtze River Urban Agglomerations. (April 2019) - Chen, Wanxu; Ye, Xinyue; Li, Jiangfeng; Fan, Xin; Liu, Qingsong; Dong, Weichuan
Highlights: Paddy field occupation and dry land compensation is critical. Superior occupation and inferior compensation have been intensified. Farmland exploitation may degenerate the ecosystems, while farmland reclamation may generate the environmental benefits. A telecoupling analysis framework is used to analyze the dilemma and countermeasures of the CRCB policy. Abstract: This study evaluates the requisition–compensation balance of farmland (RCBF) policy with the telecoupling framework of "quantity-quality-productivity-ecological balance" in the middle reaches of Yangtze River Urban Agglomerations (MRYRUA) in China from 1995 to 2015. The RCBF index characterizes the quantity balance of farmland, while the quality balance is measured by examining the differences of physical elements (elevation, slope, soil texture, soil erosion, organic content, and pH value) between the requisitioned and compensatory farmland. The productivity balance is identified through the estimated grain yield, and the ecosystem services value (ESV) model is used to examine the ecological balance of the RCBF. The issues of "paddy field occupation and dry land compensation" and "superior occupation and inferior compensation" are proven to be critical in the MRYRUA, while the productivity of the requisitioned and compensatory farmland have reached a balance during the study periods. Two vicious circles and a serial of spillover effects are shown as the results of telecoupling. We suggest that more attention should be placed on land reclamation and land consolidation in order to avoid over-reliance on land exploitation. The findings have important implications for environmental protection, ecological compensation decisions, and land use sustainability.